(untitled) (Journal Of Educational and Psychological Researches, 2012)
The importance the youth because they are the fundamental basis of the development process so to be an emphasis on their active participation in community building . When there is community participation the democratization . Will tazzfa community because the process of community participation and develop the capacity to carry on almsoulin among young people and will lead to culture of self confidence and alhawwar walaklauah . Beactivted and community participation for young people through several channels . Family , school , media and civil society organization as we discussed in the research factrstnat hinder community participation of youth in development . The most important factors that hinder participating based on patriarchal contradictory elements of some of the directions of disabled almadewaldehor present socondy almadrshnat student participation in the opinions ideas and criticism another factor whicnaffecr the community and society avadath maihamlh traditions to young of the directions of